Practical Learning Model Assisted by Mobile Workshop for Enhancing Practical Skills and Entrepreneurial Spirit for Prospective Vocational High School Graduates - Fakhri, Faizal; Hadromi, Hadromi; Widjanarko, Dwi (Journal of Vocational and Career Education, 2018)
The problem revealed in this practical learning model developing assisted by mobile workshops research is to find out the validity, practicality and effectiveness of the learning model assisted by mobile workshop for students' practical skills and entrepreneurial spirit. Research conducted using research and development (R & D) methods with a 4D development model (define, design, develop, disseminate) limited scale trials with the technique before-after without control group design. The practical learning model applies 6 (six) aspects of practical skills and 4 (four) aspects of students' entrepreneurial spirit. The results showed that the learning model assisted by mobile workshop was declared valid based on the average score of Expert 1 cycle II of 3.57 and Expert 2 of cycle II with a mean score of 3.74 with a very valid category and very feasible to use. Based on the practicality questionnaire given to 42 students and 3 teachers the results were "very practical". Based on the assessment of effectiveness using the t test for a 95% significance level obtained the probability value / p value of the test t paired is 0,000 < 0,05. The gain test result with a mean score 0.5359 means that there isÂ  increasing level of practical skills and an entrepreneurial spirit of the students after implementing the practical learning model assisted mobile workshop in medium scale, so that the practical learning model assisted mobile workshop is proven to enhance the practical skills and entrepreneurial spirit of the students.